PARENTS' LEGAL RESPONSIBILITIES FOR THE USE OF INFORMATION MEDIA AND ELECTRONIC TRANSACTIONS BY CHILDREN IN THE CURRENT DIGITAL ERA - Tomson Situmeang; I Dewa Ayu Widyani; Andree Washington (Honeste Vivere, 2023)
In the digital era, especially during the current COVID-19 pandemic, the demands of parents' roles and responsibilities towards children, especially to build relationships and communicate with children, are very important and relevant. Digitization in all aspects of life after the COVID-19 pandemic has changed the way people live in general and are "forced" to enter and live in the digital world. Stand on this, the law exists to give meaning to family life, in the form of parental responsibility and children’s respect for parents, even in the digital era.